Foreign Bank Entry : Experience, Implications for Developing Countries, and Agenda for Further Research - Clarke, George (World Bank, Washington, DC, 2014)
In recent years, foreign bank participation has increased tremendously in several developing countries. In Argentina, Chile, the Czech Republic, Hungary and Poland, for example, more than fifty percent of banking assets are now in foreign-controlled banks. In Asia, Africa, The Middle East, and the former Soviet Union, the rate of entry by foreign banks has been slower, but the trend is similar. Although the number of countries welcoming foreign banks is growing, many questions about foreign bank entry are still being debated, including: 1) What draws foreign banks to a country? 2) Which banks expand abroad? 3) What do foreign banks do once they arrive? 4) How does the mode of a bank's entry - for example, as a branch of its parent, or as an independent subsidiary company - affect its behavior? The authors summarize current knowledge on these issues. In addition, since the existing literature focuses heavily on industrial countries, they put forth an agenda for further study of the effects of foreign bank entry in developing countries.